Association of Neuropathic Pain with Anxiety Severity in Cancer Patients: A Cross-Sectional Analytic Study - Alfebrino, Alfebrino; Zainumi, Cut Meliza; Ihsan, Muhammad (Faculty of Medicine, Universitas Padjadjaran, 2026)
Background: Pain and anxiety are highly prevalent interrelated symptoms in cancer patients; however, the relationship between specific pain mechanisms and anxiety severity remains insufficiently characterized. This study aimed to examine the association between mechanism-based pain classification and anxiety levels in cancer patients. Methods: A cross-sectional study was conducted among 103 cancer patients attending a tertiary pain clinic. Pain mechanisms were classified using the PainDETECT Questionnaire (PDQ) into nociceptive, unclear/mixed, or neuropathic categories. Anxiety severity was assessed using the Generalized Anxiety Disorder-7 (GAD-7) scale. Associations were analyzed using correlation tests, the Kruskal–Wallis test, and Fisher’s exact test, with p<0.05 considered statistically significant. Results: Neuropathic pain was the predominant mechanism (57.3%). Anxiety severity differed significantly across pain types (p=0.004), with patients experiencing neuropathic pain demonstrating higher mean GAD-7 scores (12.98) compared with unclear/mixed (11.82) and nociceptive pain (11.50) (p=0.009). Moderate-to-severe anxiety was present in 98.3% of patients with neuropathic pain. Younger age was weakly but significantly correlated with higher anxiety levels (r=–0.224; p=0.024). Discussion: The findings suggest that neuropathic pain contributes to a heavier psychological burden than other pain types. Younger age was also identified as a vulnerability factor for anxiety, potentially due to greater psychosocial impact in this age group. Conclusion: Pain mechanisms are significant predictors of anxiety in cancer patients, with neuropathic pain associated with greater psychological vulnerability. Younger patients also exhibit higher anxiety levels. These findings emphasize the clinical necessity of integrating psychological screening with mechanism-based pain assessment.